Impact of Celebrity Endorsement on Brand Image: A Survey of GSM Users in Umuahia Urban, Abia State - Nto, Chioma Philips O.; Kalu, Alexanda Ogbonna Udu (Archives of Business Research, 2019)
This study focuses on the influence of celebrity endorsement on brand image among GSM users in Umuahia Urban. In other to achieve the objective of this study, two research hypotheses were formulated and the generated data were analyzed and tested using the Pearson moment correlation analysis with the aid of Statistical Package for Social Sciences (SPSS .22). Data for the study were collected through questionnaire administered on 200 respondents which constituted the sample size. The study found a positive and significant relationship between celebrity endorsement and all the metrics of brand image considered in the study. Significantly, the study showed a strong and positive correlation between celebrity endorsement and brand awareness, while the relationship between celebrity attractiveness and brand personality is found to be moderate. The paper therefore concluded that celebrity endorsement is a needful communication strategy for building a strong brand image, and recommends that marketers must be careful enough to ensure a good brand ambassador is chosen so as to raise the unique selling proposition of the firm to new heights.